MOONLIGHTING IN NIGERIA: A DUAL-PROFESSION EXAMINATION OF JOB OUTCOMES FOR ACADEMICS AND MEDICAL PRACTITIONERS - Afolabi, Chukwuma Ebenezer; Fasina, Grace Oluwakemi (Research Journal of Economics and Sustainable Development, 2024)
This study aims to investigate the impact of moonlighting on job commitment, retention, and satisfaction among academic staff and medical practitioners in Southwest Nigeria. With understaffing becoming a more common issue in universities and healthcare clinics, employees are taking on more jobs, impacting their primary job performance. Therefore, this study explores the cumulative effects of moonlighting on employee motivation, satisfaction, and performance levels using equity theory and Herzberg’s twofactor theory as frameworks. The study reveals that moonlighting is negatively impacting employees’ work quality, absenteeism, and weariness, leading to a subsequent need for favorable employment regulations, an enabling atmosphere, and attractive non-salary benefits. To achieve these goals, the study recommends that employers provide adequate and suitable working conditions to ensure that employees perform at their highest level. Additionally, regular staff development programs should be implemented, allowing employees to become more efficient and productive while staying current with industry trends. Overall, this study highlights the need for further research to address the impact of moonlighting on developing countries' health and education sectors and calls for joint efforts to combat the issue.